Investigating the relationship between customer experience components on commitment and customer engagement behaviors in the retail industry - Alireza Naalchi Kashi (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research in the first stage was to examine the mediating role of customer commitment on the relationship between customer's experience and engagement behaviors, and in the second stage to investigate the relationship between customer experience components on commitment and customer engagement behaviors and commitment on customer engagement behaviors. This research is applicable and of a descriptive-survey type. The statistical population of this research was all customers of Ofogh Korosh stores in Isfahan city, the sample size was determined based on Cochran's formula for an unlimited population of 384 people; and for greater certainty, 429 questionnaires were collected and analyzed. A simple random method was used for sampling, and a questionnaire was used to collect data. Also, the reliability of the research was evaluated and confirmed through Cronbach's alpha coefficient. In order to test the hypotheses, the structural equation model and Smart PLS version 3 and SPSS version 19 software were used. Data analysis showed that there is a significant relationship between customer experience and customer engagement behaviors with the mediating role of customer commitment. There is a positive and significant relationship between the components of customer experience (cognitive, emotional, physical/sensory, and social) with customer commitment. In addition, there is a positive relationship between customer commitment and customer engagement behaviors. There is a significant relationship between customer experience components (cognitive, emotional, physical/sensory, and social) with customer engagement behaviors (acceptance, cooperation, feedback, helping others, and positive word-of-mouth advertising). Therefore, by focusing on providing positive customer experiences that strengthen commitment, organizations can drive engagement behaviors and cultivate a loyal customer base. Extended Abstract Introduction Creating an excellent customer experience is a major and challenging issue in marketing (Saeedi et al, 2023; Raeisi Ziarani et al, 2023) and for companies in today's competitive world, it has created a competitive environment where four out of five companies compete with each other for customer experience; and success belongs to those companies that create a better experience for customers (Saeedi et al, 2022); because creating a positive experience is the basis for business growth and development (Raeisi Ziarani et al, 2023). Pleasant experiences can give customers a higher perception of service quality and encourage them to provide suggestions and information to retailers and other customers (Raeisi Ziarani et al, 2023). Customer experience plays an important role in shaping customer commitment (Yingfei et al, 2022). Studies have shown that customers who have a positive social experience interacting with retail employees or other customers contribute to the retailer and other customers and may develop a committed and emotional relationship with the retailer (Raeisi Ziarani et al, 2023; Merdiaty et al, 2023). 2022). Therefore, organizations should prioritize providing exceptional customer experiences to strengthen customer commitment. In addition, commitment affects customer engagement behaviors and causes customer engagement (Chen et al, 2010). In the field of retail, companies must establish strong relationships between the company and the customer by involving customers. Customer engagement is defined as the behavioral disclosure of customers towards a company, product or brand that originates from motivational stimuli (Xuan Do et al, 2020; Barari et al, 2021). According to social exchange theory, customers committed to a particular retailer are willing to support the company as a sign of mutual involvement (Anaza & Zhao, 2013). The social exchange theory shows that when customers are satisfied with the services received from a company, they consider the company as their trading partner to provide superior services and are motivated to voluntarily engage in extra-role behaviors (Raeisi Ziarani et al., 2023). Therefore, customers who gain effective social experiences from interacting with retail employees or other customers are more inclined to help retailers and other customers (Roy et al, 2022). In addition, customer engagement is influenced by customer experience factors and plays a central role in the value creation process that can be beneficial for both parties (Honora et al, 2023). Raeisi Ziarani et al. (2023); Syahputra & Murwatiningsih (2023); and Merdiaty et al. (2022) state that in order to achieve positive customer engagement, companies must create a positive experience for customers. Studies indicate that customers who have positive experiences with the brand are more likely to participate in behaviors such as brand advisors, participating in loyalty programs, and providing feedback (Shukla et al, 2016). But when the customer's evaluation of the brand experience is negative, he tends to inappropriate behaviors such as not providing feedback (Chen et al, 2021). As a result, the researcher of this study seeks to answer two questions: Does commitment have a mediating role on the relationship between experience and customer engagement behaviors or not? and do the components of customer experience have an effect on the commitment and behavior of customer engagement or not? Theoretical framework Customer experience Customer experience is considered as direct or indirect customer interactions that are influenced by cognitive, emotional, physical/sensory and social elements in the interaction process (Roy et al, 2022). A pleasant experience makes the customer return to use the services provided by the company (Syahputra & Murwatiningsih, 2019). Customer commitment Commitment is defined as a multidimensional structure that includes emotional, normative, economic, compulsory and habitual components, and both parties desire to maintain long-term relationships (Roy et al, 2022). Studies have shown that customers who have a positive experience interacting with retail employees develop a committed and emotional relationship with the retailer (Merdiaty et al, 2022) and if they have a poor experience, they are less likely to communicate with the brand or retailer (Shukla et al, 2016). Customer engagement behaviors Customer engagement is defined as a psychological state that reflects interactive and creative experiences of customers with a company (Verleye et al, 2014). Customers will believe that the company cares about their interests and needs when they feel that the company has the ability and integrity necessary to provide good answers to customers during interactions with them (trusting the company). Therefore, customers will be committed to the company, and this will increase their willingness to create and maintain quality relationships with the company (Roy et al, 2022; Wijaya & Simamora, 2023). Paisri et al., (2022) investigated customer experience and commitment on electronic word of mouth advertising and revisit intention. The results showed that there is a positive relationship between all components of customer experience (educational, entertainment, aesthetic, and escape) and commitment (emotional and continuous). Affective commitment mediates the relationship between entertainment experiences, escape from reality, electronic word of mouth and revisit intention. Finally, they stated that managers should focus on customer experience to create customer commitment, positive electronic word of mouth, and revisit intention. Mozaffari Asrami & Yousefi Saeedabadi (2021) investigated the effect of brand experience on customer engagement, considering the mediating role of service quality. The results showed that brand experience has a significant effect on customer interaction. Also, brand experience affects the quality of service. In addition, service quality has a direct effect on customer interaction; and finally, service quality plays a mediating role on the relationship between brand experience and customer engagement. Research methodology The present study is applicable in terms of purpose, and descriptive-survey in terms of data collection. The statistical population of this study is all the customers of Ofogh Korosh stores in Isfahan city. The sample size was determined based on Cochran's formula for an unlimited population of 384 people; and for greater certainty, 429 questionnaires were collected and analyzed. Simple random method was used for sampling, and closed questionnaire of Roy et al. (2022) with a five-point Likert scale was used to collect data. Research findings In order to test the hypotheses, the structural equation model was used through the partial least squares method, and Smart PLS version 3 and SPSS version 19 software were used. The findings of the research showed that based on the significant values ​​related to the hypotheses, the main hypothesis and the first to ninth sub-hypotheses were confirmed except the sixth hypothesis. As the results showed, customer commitment mediates the relationship between customer experience and customer engagement behaviors (Sobel test statistic is 4.45 and is higher than 1.96). Also, there is a significant relationship between the components of customer experience (emotional, sensational, physical/sensual and social) with customer commitment (total significant coefficients are greater than 1.96). In addition, there is a significant relationship between commitment and customer engagement behaviors (the significant coefficient is equal to 7.58, which is higher than 1.96). Finally, the components of customer experience, including emotional, physical/sensual, and social, have an effect on customer engagement behaviors (total coefficients of the significance is greater than 1.96), while the cognitive component has no relationship with customer engagement behaviors (the significance coefficient is equal to 1.09, which is less than 1.96). Conclusion The purpose of this study in the first stage is to examine the mediating role of customer commitment on the relationship between experience and customer engagement behaviors, and in the second stage to investigate the relationship between customer experience components on commitment and customer engagement behaviors, and commitment on customer engagement behaviors. The results of this research is consistent with the results of Roy et al., (2022); Yingfei et al., (2022); Paisri et al., (2022); Mozaffari Asrami & Yousefi Saeedabad (2021); Chen et al., (2021); Raeisi Ziarani et al., (2023); and Barari et al., (2021). The results related to the main hypothesis showed that customer commitment mediates the relationship between customer experience and customer engagement behaviors. Therefore, it is suggested that Ofogh Korosh store should use attractive discounts and support the ideas and opinions of loyal customers in order to improve customer experience and engagement. The results related to the first to ninth sub-hypotheses (except the sixth sub-hypothesis) showed that the components of customer experience have an effect on customer commitment and engagement behaviors. Therefore, it is suggested that the store of Afogh Korosh causes customer commitment and involvement through easier transportation, offering discounts based on the purchase volume, creating a relaxing atmosphere, providing training to the employees to establish satisfactory communication. The results related to the fifth hypothesis showed that commitment has an effect on customer engagement behaviors. Therefore, it is suggested that Afogh Korosh store increases customer commitment by handling customer complaints and empathizing with front-line employees, and increasing customer interaction with the store by facilitating service delivery and requests to fill out customer feedback forms. Finally, the variables present in this research are necessary for the survival of any retail store, and not paying attention to them leads to the reduction of long-term relationships with customers, which results in the lack of profitability of the retail store. Also, buyers who are committed to a relationship show a willingness to make more efforts on behalf of the company in return for previous benefits received from the company, and are more willing to associate with the organization and help recover failed services. By increasing the level of commitment, customers gain a better understanding of what is expected of them during the exchange process and spend more time contributing to the successful delivery of the company's services in the future.